2000
DOI: 10.1136/vr.147.12.328
|View full text |Cite
|
Sign up to set email alerts
|

Presence of bovine herpesvirus 1 gB‐seropositive but gE‐seronegative Dutch cattle with no apparent virus exposure

Abstract: Two hundred and thirty-seven of 2052 cattle which had not been vaccinated against bovine herpesvirus 1 (BHV-1) were seropositive in a glycoprotein B (gB)-blocking ELISA, but seronegative in a glycoprotein E (gE)-blocking ELISA. In order to detect whether they were latently infected with BHV-1, 10 of them were treated with corticosteroids in an attempt to reactivate putatively latent virus. After successive treatments with dexamethasone and prednisolone, no virus excretion was detected and they showed no increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…However, no viral reactivation could be detected in any of the hypervaccinated gE‐seronegative animals. Moreover, no anamnestic effect of the bhv ‐1‐specific immune response typically associated with virus reactivation (Thiry and others 1983, Mars and others 2000) was observed in any of the 19 gE‐seronegative calves after their treatment with dexamethasone.…”
Section: Discussionmentioning
confidence: 90%
“…However, no viral reactivation could be detected in any of the hypervaccinated gE‐seronegative animals. Moreover, no anamnestic effect of the bhv ‐1‐specific immune response typically associated with virus reactivation (Thiry and others 1983, Mars and others 2000) was observed in any of the 19 gE‐seronegative calves after their treatment with dexamethasone.…”
Section: Discussionmentioning
confidence: 90%
“…This diagnostic tool seems particularly important in Countries in which BoHV1 is under eradication program in presence of vaccination. It is not rare the occurrence of cattle herds that, from a free status, turn to marker vaccinated status (gB+/ gE--) without apparent vaccination (Mars et al, 2000). In this situation a seroconversion against attenuated marker vaccine or BoHV1 strain naturally mutated at the immunodominant epitope level has never been demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…BoHV-2 infections have also been described in Africa, Europe, the United States, and Australia (2-4). Several European countries have reported unexplained cases of gB-positive singleton reactors and they were found to be gE-negative (5,8,13,14). In this report, we have shown that 1 out of 2 commercial competitive gB-ELISAs gave a positive result which was not confirmed by BoHV-1 plaque reduction assay, VN, or competitive gE-ELISA tests.…”
Section: Discussionmentioning
confidence: 99%